Determine the number of ordered triples of positive integers ( a , b , c ) such that a + b + c + a b + b c + a c = a b c + 1 .
This problem is shared by Kevin K .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good job!
same pinch...... I too did the same
Hey,I have a question, ab-1=(a+b)(1+2/c-1), so you stated that 2/c-1 must be an integer, but if it is not an integer, then it would be a fraction and integer=integer*fraction is a possible case, so I think its not necessary that 2/c-1 must be an integer.
I didn't assume at any point that c − 1 2 had to be an integer; I can't see that I've stated it here. In fact, I considered c − 1 2 < 1 , where it is certainly not an integer.
If a = 1 , then the given equation becomes 1 + b + c + b + b c + c = b c + 1 . But it is clear that the left-hand side is greater than the right-hand side, so there are no solutions when a = 1 . Similarly, there are no solutions when b = 1 and c = 1 .
Hence, a , b , and c must all be at least 2. Let x = a − 1 , y = b − 1 , and z = c − 1 , so x , y , and z are positive integers. Also, a = x + 1 , b = y + 1 , and c = z + 1 . Substituting into the given equation and simplifying, we get 2 x + 2 y + 2 z + 4 = x y z . ( ∗ ) This equation is symmetric in x , y , and z , so without loss of generality, assume that x ≤ y ≤ z . We can divide both sides by x y z to get x y 2 + x z 2 + y z 2 + x y z 4 = 1 .
If x ≥ 3 , then y ≥ 3 and z ≥ 3 , and x y 2 + x z 2 + y z 2 + x y z 4 ≤ 3 2 2 + 3 2 2 + 3 2 2 + 3 3 4 = 2 7 2 2 < 1 , so x = 1 or x = 2 .
If x = 1 , then equation ( ∗ ) becomes 2 + 2 y + 2 z + 4 = y z , which we can write as ( y − 2 ) ( z − 2 ) = 1 0 . This leads to the values y = 3 and z = 1 2 , and y = 4 and z = 7 .
If x = 2 , then equation ( ∗ ) becomes 4 + 2 y + 2 z + 4 = 2 y z , which we can write as ( y − 1 ) ( z − 1 ) = 5 . This leads to the values y = 2 and z = 6 .
Substituting back, we find that all the solutions in ( a , b , c ) are ( 2 , 4 , 1 3 ) , ( 2 , 5 , 8 ) , ( 3 , 3 , 7 ) , and their permutations. This gives us a total of 6 + 6 + 3 = 1 5 solutions.
Nicely done!
From AM-GM, we have
a + b + c + a b + b c + a c = a b c + 1 ≤ 6 6 a 3 b 3 c 3 = 6 a b c
Letting u = a b c , we can bound the product a b c by finding the positive values that satisfy
u + 1 ≤ 6 u
It turns out that a b c ≤ 3 4 . Next, assume WLOG that c ≤ b ≤ a . Hence, c ≤ ⌊ 3 4 ⌋ = 3 . The rest is casework.
Case c = 1 : From the original equation, a = − b , a contradiction. No solutions.
Case c = 2 : From the original equation, a = 3 + b − 3 1 0 . This yields the solutions ( a , b , c ) = ( 1 3 , 4 , 2 ) , ( 8 , 5 , 2 )
Case c = 3 : From the original equation, we have a = 2 + b − 2 5 . This yields the solution ( a , b , c ) = ( 7 , 3 , 3 ) .
Counting permutations of these three solutions, we get that there are 3 ! + 3 ! + 2 ! 3 ! = 1 5 solutions.
Eh? Isn't ⌊ 3 4 ⌋ equal to 5 ? Shouldn't it be c ≤ ⌊ 3 3 4 ⌋ ?
Yup you are correct Sreejato! I also think there's a typo
WLOG,we can assume that, a ≥ b ≥ c . At first ,we will prove that c<4. if c ≥ 4 then, a + b + b + a b + b 2 + a b ≥ L . H . S .So, a + 2 b + 2 a b + b 2 ≥ a b c + 1 ≥ 4 a b + 1 .Simplifying, a + 2 b + b 2 ≥ 2 a b + 1 .But since, 2 a b + 1 = a b + a b + 1 ≥ b 2 + a b + 1 .So,showing a b + 1 > a + 2 b we will get our contradiction. But we can write this as, (b-1)(a-2)>1 since a ≥ b ≥ c ≥ 4 this is true. For rest of the cases,some factoring and case work gives the solutions, (2,4,13),(2,5,8),(3,3,7) and their permutations which are 6+6+3=15 in total.
Suppose that a >= b >= c >= 1; We have the equation equivalents to (c + 1) (a + b) = (c-1) ( ab -1 ). Because a >=b >= c, so we have: (c - 2)^2 <= 3, so 1<= c <= 3. c = 1, no root c = 2, a = 3 + 10 /(b - 3), so 2 roots: (10, 4, 2), (8, 5, 2) c = 3, we have 1 root (3,3,7) So, we have totally 15 roots
How do you conclude that ( c − 2 ) 2 ≤ 3 ?
Problem Loading...
Note Loading...
Set Loading...
Without loss of generality, assume a ≥ b ≥ c .
Rearrange the equation as follows -
( a b − 1 ) ( c − 1 ) = ( a + b ) ( c + 1 )
This can immediately tell us that c = 1 , otherwise ( a + b ) ( 2 ) = 0 , impossible for positive a , b .
The similarity of ( c − 1 ) and ( c + 1 ) suggest we should combine them somehow for information on a and b . If we divide by ( c − 1 ) we get:
a b − 1 = ( a + b ) c − 1 1 + c = ( a + b ) ( 1 + c − 1 2 )
However, 1 + c − 1 2 is always between 1 and 3 for c ≥ 2 . This gives us a way to constrain a , b . There will be some casework afterwards, which is reduced incredibly by checking the cases c = 2 , 3 now.
.
For c = 2 ,
a b − 1 = 3 ( a + b ) a b − 3 ( a + b ) − 1 = 0 ( a − 3 ) ( b − 3 ) = 1 0
From this, ( 1 3 , 4 , 2 ) and ( 8 , 5 , 2 ) are the only solutions with c = 2 .
For c = 3 ,
2 ( a b − 1 ) = 4 ( a + b ) a b − 2 ( a + b ) − 1 = 0 ( a − 2 ) ( b − 2 ) = 5
So ( 7 , 3 , 3 ) is the only solution with c = 3 .
.
Now return to
a b − 1 = ( a + b ) ( 1 + c − 1 2 ) < ( a + b ) ( 1 + 1 ) , as c − 1 2 < 1
a b − 1 < 2 ( a + b ) a b − 2 a − 2 b − 1 < 0 ( a − 2 ) ( b − 2 ) < 5
This is satisfied, along with a ≥ b ≥ c ≥ 4 , only for a = 4 , b = 4 . Putting these values into the original gives no solution for c . (n.b. this is the only case to check; without having eliminated c = 2 , 3 first, there were 1 6 to check.)
.
The only unordered solutions are therefore ( 1 3 , 4 , 2 ) , ( 8 , 5 , 2 ) and ( 7 , 3 , 3 ) . There are 6 permutations of the first two and 3 of the last, so 6 + 6 + 3 = 1 5 overall solutions.